P203 Assessing the concordance between patient-reported ICS adherence and objective e-monitoring of ICS therapy. (11th November 2022) - d'Ancona, G; Stewart-Kelcher, N; Patel, A; Holman, N; Green, L; Lam, J; Thompson, L; Nanzer, A; Jackson, DJ; Holmes, J; Propeller Health, A; Heaney, LG; et al.
Abstract : Introduction: The prevalence of asthma and the scale of sub-optimal inhaled corticosteroid (ICS) use therein, demands efficient detection of medicines non-adherence. Several tools estimate adherence to medicines in asthma, each with varying complexity of application and limitations. The Test of Adherence to Inhalers 1 (TAI) questionnaire asks patients to rate their agreement with 10-items, and the subsequent score classifies adherence as good, intermediate or poor. A more objective, though currently less accessible tool is the electronic monitor (eMonitor), where a Bluetooth enabled sensor is attached to the inhaler device to record the date/time of each actuation. If actual use is > 75% of expected use, adherence is good. The resultant impact of guaranteed ICS use on Fractionate expired Nitric Oxide (FeNO) can then allow a judgement of pre-monitor adherence – this is the FeNO suppression test 2 (FST). Methods: Patients attending a hospital asthma clinic completed the TAI, received an eMonitor and were followed up 6 weeks later. The FST was positive if the 6-week FeNO decreased by > 42% from baseline. Results: Data for 88 patients were included, of whom 76 (86%) had good ICS adherence according to the eMonitor. 35 people had a positive FST; 12 (34%) had a TAI adherence that was designated good, 19/35 (54%) intermediate and 4 (11%) poor. In the negative FST group, 15/41 (37%) had a TAI adherence classification of good, 21 (51%) intermediate and 5 (12%) poor. Conclusion: In this cohort, a third of patients with eMonitoring/biomarker evidence to suggest suboptimal ICS adherence (that is, a positive FST) completed a TAI that over-estimated ICS use. Conversely, in the FST negative patients (likely to have been adherent prior to eMonitor initiation), almost two thirds of patients identified themselves on TAI as having suboptimal adherence. This suggests that the TAI may not accurately predict adherence or potentially, that using the eMonitor in itself encourages better adherence in the short-term. References: Plaza V et al . Test of Adherence to Inhalers Arch Bronchoneumol 2017;53 :360–1. Heaney LG et al . Remotely Monitored Therapy and Nitric Oxide Suppression Identifies Non-Adherence in Severe Asthma. American Journal of Respiratory and Critical Care Medicine 2019;199 (4):454–464.